Mythological paradigm at the primary sources of the Ukrainian culture - Volodymyr Fed (Cхід, 2013)
The article devoted to investigation of mythological ideological sources of Ukrainian spirituality in paradigmatical measurement. The accent is made on the organic relations of culture and myth realized in the mythological concept of the ideological paradigm.